Peranan Material Interior dalam Pengendalian Akustik Auditorium Bandung Creative Hub - Putra, Alnugraha Rachman; Nazhar, Ryanty Derwentyana (Waca Cipta Ruang, 2020)
Acoustics in an auditorium interior have a vital role in the continuity of activities in it. Activities in the auditorium are closely related to audio and visual, so designing an auditorium requires an acoustic control system, not only visual elements are considered, but also sound or acoustic control requires special attention. This study describes the role of interior materials in acoustic control in a multifunctional auditorium in the Bandung Creative Hub building, West Java. To determine the quality of the room acoustics under study, the research method used is descriptive analysis by processing data in the form of images, field notes, documentation, and supporting theories according to the principles of interior design science. This study concludes that the interior materials in the multifunctional auditorium in the Bandung Creative Hub Building have met the applicable standards in the acoustic control of the auditorium space. The benefit of this research is that it can be used as a benchmark for auditorium design and can be a reference for space design that requires special acoustic treatment in the future.